Allele-Specific Holliday Junction Formation: A New Mechanism of Allelic Discrimination for SNP Scoring - Yang, Qinghong; Lishanski, Alla; Yang, Wendy; Hatcher, Sandra; Seet, Henrietta; Gregg, Jeffrey P. (Genome Research, 2003)
We report here a new mechanism for allelic discrimination—allele-specific Holliday Junction formation. The Holliday Junction (HJ) is a unique DNA structure that can be formed in a sequence-nonspecific manner by routine PCR. To cause the PCR-based HJ formation to occur in an allele-specific manner, the PCR primers are manipulated such that an extra mismatch next to a SNP of interest is introduced between a target and a reference amplicon and a GC-clamp is added. Based on this new mechanism, novel SNP genotyping methods were developed, including a homogeneous fluorescence polarization (FP) competition assay that requires neither labeled primers/probes nor expensive enzymes/substrates. Using this novel genotyping technology, we were able to convert >95% of SNP sequences into genotyping assays that work well under a universal set of assay conditions and achieved 100% accuracy in clinical samples.
10.1101/gr.997703